Evaluation of implant stabilization in tubercular Spondylodiscitis: a prospective study - Maila, Sharath Kumar; Rao, Akyam Lakshman; Sunnadkal, Rajani Somappa; Krishna, Murali (International Journal of Research in Medical Sciences, 2017)
Background: Stabilization in tubercular spine is very often employed for various indications. Many papers have detailed the management strategies and outcome in the management of spinal tuberculosis. There are not many papers detailing the complications that followed stabilization in tubercular spine, which are very essential in the development of safe surgical procedures and avoiding complications. In the present study 50 patients who were stabilized for tubercular spine were followed up for a period of 2 years. Various complications encountered during this period were detailed with a possible mechanism for the same and a strategy to address such a complication. Methods: 50 consecutively available patients who underwent a standard stabilization procedure for spinal tuberculosis and were available for follow-up for a period of 2 years were subjects of the study. All the complications encountered in these patients during the follow-up period were noted and were managed. Results: Mechanical failure of the implant was the most commonly encountered complication. Neurological complications included progressive neurologic deterioration, hoarseness of voice, cauda equina syndrome, foot drop. Persistent worsening of pain, DVT and pressure ulcers were the complications encountered that are not specific to a region of spine. Conclusions: Stabilization is not without complications in tubercular spine. But with strict adherence to guidelines the complications can be minimal and are not dismal.